PUBLIC RELATIONS SEBAGAI UNSUR PEMBENTUK KEPRIBADIAN ORGANISASI - Martono Kunarso (JURNAL MITRA MANAJEMEN, 2012)
AbstractNot many know that Public Relations is a very strategic approach toinfluencing the way of thinking or worldview of a society by using the concepts ofcommunication. By using techniques appropriate communication, the practice ofPublic Relations will be a very important force for an organization, and will be areflection of personality organization.Roger Haywood, a leading public relations practitioners from the UKmentioned, that there is indeed a successful organization or company relying on thestrength of the leader's personality, without utilizing the services of public relations,but along with the way the organization is becoming increasingly ineffective.Haywood further went on to say